An Empirical Analysis of the Impact of Corporate Governance on Executives Compensation in State-owned Listed Enterprises in China - Li, Muzi (2020)
Among the various agency relationships within the company organization, the senior executives of the companies are the main decision makers. The performance of the company, the development prospect of the company and the realization of the interests of the shareholders of the company are all related to the selection and decision-making of the senior executives to a great extent. Therefore, the agency relationship between the shareholders and the senior executives of the enterprises undoubtedly has a prominent and important position. Through the reasonable corporate governance structure to improve the efficiency of salary arrangements, of course, has been the concern of around the world. If the corporate governance is reasonable, it can ease the agency problem of shareholders and managers caused by the separation of ownership and management rights. Besides, it could also reduce the cost of agency by keeping the interests of managers and shareholders more consistent. The purpose of this research is to verify the impact of corporate governance on senior executives compensation in Chinese state-owned enterprises through empirical analysis. Based on the review of relevant theory and literature, this paper takes A-share state-owned listed companies in Shenzhen and Shanghai stock exchanges as samples, collects relevant data from CSMAR database, and uses descriptive statistics and multiple linear regression methods. After that, this paper analyzes the impact of corporate governance structure on executive compensation in state-owned enterprises, and provides suggestions for improving the effectiveness of corporate governance, as well as some reform measures of executive compensation. The results of regression reveal that in the sample companies, executive compensation is positively correlated with the size of the board of directors, the duality of CEO and the proportion of executives' shareholding. Besides, the relationship between executive compensation and ownership concentration and the proportion of independent directors on the board is not significant. Furthermore, this paper analyzes the above regression results, combined with the status of the corporate governance structure and executive pay in Chinese state-owned listed companies. Finally, the paper offers the following suggestions on the improvement of corporate governance structure and the standardization of executive compensation in Chinese state-owned enterprises. 3 1.Establish the appropriate board size. 2.Eliminate the duality of CEO. 3.Combine executive compensation with long-term performance of the company, and develop equity incentive supporting policies. 4.Improve the supervision and evaluation mechanism of non-executive directors, build the accountability system of non-executive directors, and link the remuneration of non-executive directors with firm performance. 5. Form multiple equity identities and clarify the subject of property rights.